Resolution of the Long Conflict in Papua for Equitable National Development - Chasib, Abdul (Lembaga Ketahanan Nasional Republik Indonesia, 2024)
Purpose: This study aims to analyse efforts to resolve the Papua conflict to achieve equitable national development, focusing on the role of Special Autonomy (OTSUS) policies, local leaders' involvement, and community-based security strategies. Study Design/Methodology/Approach: Using a qualitative approach through a comprehensive literature review, this study adopts the theoretical frameworks of Social Resilience and Sustainable Development, identifying factors that influence social stability in Papua. Data was drawn from previous studies, policy document analysis, and relevant theories to explore bureaucratic challenges, unequal access to public services, and the significant role of local customary and religious leaders in strengthening social cohesion. Findings: The findings indicate that the OTSUS policy has yet to succeed in improving the quality of life for the people of Papua, particularly in remote areas. Bureaucratic factors, weak law enforcement, and overlapping regulations hinder social integration and increase the community's dependence on external aid. Integrating local customary and religious leaders in development project planning and oversight has proven to increase community acceptance, reduce conflict, and strengthen local resilience. Additionally, community intelligence-based security strategies and effective use of social media are essential to counter separatist propaganda. Originality/Value: This study highlights the importance of a culturally grounded, collaborative approach to building social and economic resilience in Papua, offering a new perspective on sustainable development strategies relevant to regions with similar conflict dynamics.